Ambrosio Rabanales. Una vocación por el lenguaje - Jobet, Jorge (Revista Chilena de Humanidades, 2016)
The author emphasizes the academic quality of the Facultad de Filosofía y Educación of the Universidad de Chile during the mid XXth century. He situates the begining of the research and teaching work done by the linguistic Ambrosio Rabanales in that time, examining his scientific task until the present and demonstrating the importance of the contributions of this specialist.